Constructive Aspects of Functional Analysis lectures given at a summer school of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Erice (Trapani), Italy, June 27-July 7, 1971 - SpringerLink (Online service). (Heidelberg, Germany Springer Berlin, 2011)
A constructive approach to optimal control.- R. Glowinski: Méthodes itératives duales pour la minimisation de fonctionnelles convexes.- J.L. Lions: Approximation numérique des inéquations dévolution.- G. Marchuk: Introduction to the methods of numerical analysis.- U. Mosco: An introduction to the approximate solution of variational inequalities.- I. Singer: Best approximation in normed linear spaces.- G. Strang: A Fourier analysis of the finite element variational method.- M. Zerner: Caractéristiques d?approximation des compacts dans les espaces fonctionnels et problèmes aux limites elliptiques.
A constructive approach to optimal control -- R. Glowinski: Méthodes itératives duales pour la minimisation de fonctionnelles convexes -- J.L. Lions: Approximation numérique des inéquations d?évolution -- G. Marchuk: Introduction to the methods of numerical analysis -- U. Mosco: An introduction to the approximate solution of variational inequalities -- I. Singer: Best approximation in normed linear spaces -- G. Strang: A Fourier analysis of the finite element variational method -- M. Zerner: Caractéristiques approximation des compacts dans les espaces fonctionnels et problèmes aux limites elliptiques.
Electronic reproduction.
Keywords: Functional analysis; Mathematics